2002
DOI: 10.1002/cne.10244
|View full text |Cite
|
Sign up to set email alerts
|

Firing features and potassium channel content of murine spiral ganglion neurons vary with cochlear location

Abstract: Neurons from varied regions of the central nervous system can show widely divergent responses to electrical stimuli that are determined by cell-specific differences in ion channel composition. The well-ordered and highly characterized peripheral auditory system allows one to explore the significance of this diversity during the final stages of postnatal development. We examined the electrophysiological features of murine spiral ganglion neurons in vitro at a time when recordings could be made from the cell bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
210
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 167 publications
(226 citation statements)
references
References 79 publications
14
210
2
Order By: Relevance
“…Indeed, SGNs reacted positively to antibodies against Kv4.2 and KCNE3, and the two proteins were co-localized. In contrast, we did not detect positive staining with antibodies against Kv4.3, consistent with the results of previous studies (35,36).…”
Section: Underlying Changes In Membrane Currents In Kcne3supporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, SGNs reacted positively to antibodies against Kv4.2 and KCNE3, and the two proteins were co-localized. In contrast, we did not detect positive staining with antibodies against Kv4.3, consistent with the results of previous studies (35,36).…”
Section: Underlying Changes In Membrane Currents In Kcne3supporting
confidence: 93%
“…To extend our study further, we rationalized that at least one of the Kv channels, under the regulation of KCNE3, would generate a transient current. Among the transient current channels in SGNs is Kv4.2 (35,36). We expressed mouse Kv4.2 in CHO cells, either singly or co-jointly with KCNE3.…”
Section: Underlying Changes In Membrane Currents In Kcne3mentioning
confidence: 99%
“…Our analysis suggests that the new isoform has a longer UTR than the canonical form, potentially with a previously unrecognized role in translational regulation. KCNB1, found in the mouse dataset was identified previously by PCR in X. laevis inner ear (Varela-Ramirez et al 1998), while KCNC1 was immunolocalized previously in mouse spiral ganglion (Adamson et al 2002) and developing chick cochlear ganglion and hair cells (Zhou et al 2001). Absent from cDNA libraries was Kv4.2 (KCND2), which is found in chick and mouse cochlear ganglion and hair cells (Adamson et al 2002;Rivolta et al 2002;Sokolowski et al 2004).…”
Section: K+ Channelsmentioning
confidence: 87%
“…Studies of voltage-gated ion channel expression in inner ear tissues (Adamson et al 2002;Davis 2003) and expression of ionic currents during the development of hearing (Fuchs and Sokolowski 1990;Mammano and Ashmore 1996;Kros et al 1998;Michna et al 2003) provide evidence for the fundamental importance of ion channels in defining cellular specialization.…”
Section: Introductionmentioning
confidence: 99%
“…To follow up on the Hodgkin-Huxley sodium channels, a modern survey of the type I SGN in mice revealed Nav1.6 channel subunits located at all nodes of Ranvier with particularly higher densities at the unmyelinated afferent process innervating the IHC layer and the nodes flanking the soma (Hossain et al 2005). In end-stage postnatal development murine type I SGN, Adamson et al (2002) found several potassium channel subunits. Specifically, the highfrequency basal neurons were dominated by highthreshold fast-delayed rectifier Kv3.1, low-threshold Kv1.1, and calcium-activated K + subunits, while the low-frequency apical neurons showed a majority of inactivating Kv4.2 subunits known for extending the latency of spiking near threshold.…”
Section: Mechanisms and Modelsmentioning
confidence: 98%